Inclusion of optic nerve involvement in dissemination in space criteria for multiple sclerosis - Brownlee, Wallace J; Miszkiel, Katherine A; Tur, Carmen; Barkhof, Frederik; Miller, David H; Ciccarelli, Olga (Neurology, 2018)
To investigate the effect of including optic nerve involvement in dissemination in space (DIS) criteria for diagnosis of multiple sclerosis (MS) in patients with clinically isolated syndrome (CIS). We studied 160 patients with CIS: 129 with optic neuritis (ON) and 31 with non-ON CIS. MRI brain/spinal cord was done at the time of presentation and a follow-up MRI brain after 3-12 months. We evaluated optic nerve involvement clinically or with visual evoked potentials (VEPs, n = 42). We investigated the performance of the McDonald 2017 DIS criteria and modified DIS criteria including optic nerve involvement for development of clinically definite MS after ∼15 years. In the ON group, including symptomatic optic nerve involvement identified an additional 15 patients with DIS. The modified DIS criteria that included optic nerve involvement were more sensitive (95% vs 83%) and more accurate (81% vs 78%) than the McDonald 2017 DIS criteria, but less specific (57% vs 68%). In combination with dissemination in time criteria, the modified DIS criteria remained more sensitive (83% vs 74%) and accurate (81% vs 75%), and the specificity was the same (77%). Including asymptomatic optic nerve involvement in DIS the non-ON group did not identify any additional patients and the performance of the McDonald 2017 criteria and the modified criteria was the same. The inclusion of symptomatic optic nerve involvement in DIS in patients with ON improved the overall performance of MS diagnostic criteria. Including asymptomatic optic nerve involvement in DIS in patients with a non-ON CIS may be of limited value. This study provides Class III evidence that for patients with suspected MS, inclusion of symptomatic optic nerve involvement in DIS criteria improves the overall performance of diagnostic criteria for MS.